2022
DOI: 10.1186/s12913-022-07832-7
|View full text |Cite
|
Sign up to set email alerts
|

Opioid treatment program safety measures during the COVID-19 pandemic: a statewide survey

Abstract: Background Opioid treatment programs (OTPs) serve as daily essential services for people with opioid use disorder. This study seeks to identify modifications to operations and adoption of safety measures at Pennsylvania OTPs during the COVID-19 pandemic. Methods A 25-min online survey to clinical and administrative directors at all 103 state-licensed OTPs in Pennsylvania was fielded from September to November 2020. Survey domains included: 1) chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…Additional domains reported in a separate manuscript include procedures adopted for COVID safety and risk mitigation. 24 Clinical directors were asked to indicate which services and practices were used before versus after the start of the COVID-19 pandemic. These items included a combination of multiple choice and free response questions.…”
Section: Methodsmentioning
confidence: 99%
“…Additional domains reported in a separate manuscript include procedures adopted for COVID safety and risk mitigation. 24 Clinical directors were asked to indicate which services and practices were used before versus after the start of the COVID-19 pandemic. These items included a combination of multiple choice and free response questions.…”
Section: Methodsmentioning
confidence: 99%
“…The Coronavirus Aid Relief and Economic Security (CARES) Act, passed in 2020, allowed the Bureau of Prisons to release nonviolent, pretrial prisoners to expanded home confinement, which alleviated COVID‐related risks for some. However, rapid release without assurance of continuity of care placed released prisoners who struggled with opioid use disorder at risk of relapse (Bandara et al, 2022; Dadiomov et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Although prior research suggests service providers including methadone counselors at OTPs can be a source of enacted and anticipated stigma for their clients [123][124][125][126], these data suggest supportive providers can also have positive influences on their clients. Other studies have reported operational challenges in MOUD provision including staffing reductions and staff turnover at OTPs and office-based treatment programs during the pandemic [127,128], which may be disruptive to maintaining supportive relationships between clients and their providers as well as the clients' engagement in substance use disorder treatmentrelated services. Substance use disorder treatment programs need the resources to facilitate the retention of trained service providers who may have long-standing relationships with their clients.…”
Section: Discussionmentioning
confidence: 99%